Group management in rice production an action research - Mohammed Hussain M (Department of Agricultural Extension, College of Agriculture, 1992)
The study “Group management in rice production – an action research” was conducted in Punchakari of Kalliyoor Panchayat, Trivandrum. The study was aimed at to analyse reasons for the success or failure of earlier group approaches and also to analyse the constraints in increasing rice production. It was planned to develop and implement an action programme to overcome the identified constraints through group management. 34 farmers in an area of 10 acres were selected for the study. The research design followed in this action research study was that of ‘before and after experiment’ type, in which the experiment had the respondent’s participation in planning, implementing and evaluation and with an action research component of utilizing the results of the study for further refinement of the group management approach through continuous monitoring and evaluation of the entire programme. A suitable technology package was identified to overcome the selected constraints and introduced in the study area. The impact of the action programme on the selected socio psychological and economic variables was closely monitored and evaluated. The most important reasons for the failure of earlier group approaches were : ‘the political system does not permit’, /group approach ‘possible only when there is continuous leadership’, ‘group approach dies out when external leadership is withdrawn’, ‘no knowledge about group-mamagement’, ‘farmers are not co-operative’, ‘heterogenous group members are more in villages’, ‘no proper machinery to popularize group management’, less scope for unanimous decision’, ‘no proper extension guidance’, ‘no proper guidance from Government side’, ‘inadequate number of voluntary organisations’, ‘public involvement is less’. The nature of content reflected in the results on the constraints in increasing rice production were : ‘non availability of inputs’, ‘high cost of inputs’, ‘incidence of pests and diseases’, labour related problems’, ‘marketing’, ‘drainage’, and ‘lack of technical advice’. There was a significant change on the favourable side in the use of information sources by the respondents exposed to group management approach. The changes brought in the adoption of package of practices through group management approach were significant. Group management approach had brought in favourable changes in the character of social participation of respondents. Group management approach had played a vital role in enhancing the knowledge level about high yielding varieties of rice cultivations. There occurred a gradual but a favourable improvement in the cosmopoliteness of the respondents over group management approach period. There was a significant favourable change in the extension orientation of respondents through group-management. The respondents in the study area had changed significantly with regard to their management orientation due to group management efforts. Group management approach had influenced the attitude of respondents favourably towards it. The group cohesiveness was improved among the members of farmers as a result of group activities. There was a positive significant relationship developed between the yield obtained by the respondents and group management efforts. The net income from rice cultivation was increased considerably due to continuous exposure to group management approaches. There was marked significant reduction in the cost of cultivation of rice noticed for all the operations selected for/the study except harvesting over the four crop seasons as a result of group management. However a slight increase in the cost of cultivation of different operations noticed other than transplanting and manures and manuring during the follow up crop season when the Researcher’s supervision was withdrawn. The extension method, field visit was preferred much for all the package of practices of high yielding varieties of rice cultivated in the study area. Farmer’s training, group discussion and individual contact were found to be preferred next best in their sequence during the post exposure periods of group management approaches.